From Trainer to Agile Learning Facilitator How Teaching and Learning Works in Digital Times - Sammet, Jürgen; Wolf, Jacqueline (Springer Berlin Heidelberg : Imprint: Springer, 2022)
VIII, 128 p. 36 illus., 2 illus. in color.